The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Impact of wildfires on sediment quality in estuaries in New South Wales, Australia - Thayanne L. Barros; Mariana Mayer-Pinto; Katherine A. Dafforn; Stuart L. Simpson; Mark Farrell; Sally A. Bracewell; Emma L. Johnston (Chemosphere, 2025)

We are what ‘we’ eat: How do close social relationship dynamics in the household impact the sustainability of diets? - Tess Davis; Sophie Duncan; Rebecca Gregson; Emma Garnett; Jared Piazza; Sharon Simpson; Esther K. Papies (Appetite, 2025)

Comprehensive method to detect nitazene analogues and xylazine in wastewater - Emma L. Keller; Brock Peake; Bradley S. Simpson; Jason M. White; Cobus Gerber (Environmental Science and Pollution Research, 2025)
A class of novel synthetic opioids, nitazenes, have infiltrated the illicit drug market worldwide. Their high potency leading to overdose and fatality is a public health concern. Xylazine is a non-opiate sedative typically used for veterinary applications. The drug has recently appeared as an adulterant in the informal drug market, particularly within opioid drugs such as fentanyl and heroin. Determining the extent of use of these drugs is challenging due to low levels consumed. Wastewater analysis has been applied to monitor novel psychoactive substance use at a population level. This study presents the validation of a sensitive analytical method for the detection and quantification of trace levels of nitazenes and xylazine in wastewater. A solid phase extraction method was employed, yielding a concentration factor of 1000-fold. The method was applied to wastewater samples collected in Australia. Five different nitazenes were found near the limit of detection and quantitation levels, with detection frequencies ranging from 3 to 6% of all samples analysed. Xylazine was detected at a higher detection frequency (26% of all samples analysed). The method presented in this study could be used as an early warning system to track the use of xylazine and nitazenes internationally.

Half a century of citizen science tag-recapture data reveals stock delineation and cross-jurisdictional connectivity of an iconic pelagic fish - Belinda K. Goddard; Tristan A. Guillemin; Hayden T. Schilling; Julian M. Hughes; Stephanie Brodie; Corey P. Green; Robert Harcourt; Charlie Huveneers; Daniel Ierodiaconou; Iain M. Suthers; Matthew D. Taylor; Sean R. Tracey; et al. (Reviews in Fish Biology and Fisheries, 2024)
Tag-recapture programs to monitor the movements of fish populations are among some of the longest-running citizen-science datasets to date. Here, using half a century of yellowtail kingfish ( Seriola lalandi, Carangidae) tag-recapture data collected through citizen-science projects, we report novel insights into population connectivity in Australia and New Zealand (NZ). Despite the importance of kingfish in commercial and recreational fisheries, substantial knowledge gaps about their stock structure and connectivity between jurisdictions hinder current management efforts. Between 1974 and 2022, 63,432 releases and 4636 recaptures (7.3%) of tagged kingfish were collected in Australia and NZ. Most tagged individuals (51.4%) were recaptured within 10 km of their original release location up to 14 years post-release (mean: 225 days), indicating some degree of site fidelity. However, 656 (14.2%) kingfish were recaptured over 100 km from their release location, with one fish travelling at least 2834 km in 702 days. Seasonal variability was evident for releases and recaptures, with more releases occurring in summer and autumn in most jurisdictions. Network analysis of recaptures revealed no connectivity between tagged kingfish from western and eastern Australia, supporting genetic delineation. By contrast, extensive connectivity exists across eastern Australia and NZ, with 87 kingfish moving between five Australian state jurisdictions, 316 individuals travelling across 15 bioregions and six kingfish moving between Australia and NZ. Our findings provide important new insights into the structure and connectivity of the eastern Australia kingfish stock and suggest increased collaboration between state and international fisheries jurisdictions may support improved stock assessment and management.

Germline copy number variants and endometrial cancer risk - Cassie E. Stylianou; George A. R. Wiggins; Vanessa L. Lau; Joe Dennis; Andrew N. Shelling; Michelle Wilson; Peter Sykes; Frederic Amant; Daniela Annibali; Wout De Wispelaere; Douglas F. Easton; Peter A. Fasching; et al. (Human Genetics, 2024)
Known risk loci for endometrial cancer explain approximately one third of familial endometrial cancer. However, the association of germline copy number variants (CNVs) with endometrial cancer risk remains relatively unknown. We conducted a genome-wide analysis of rare CNVs overlapping gene regions in 4115 endometrial cancer cases and 17,818 controls to identify functionally relevant variants associated with disease. We identified a 1.22-fold greater number of CNVs in DNA samples from cases compared to DNA samples from controls ( p = 4.4 × 10 –63 ). Under three models of putative CNV impact (deletion, duplication, and loss of function), genome-wide association studies identified 141 candidate gene loci associated ( p < 0.01) with endometrial cancer risk. Pathway analysis of the candidate loci revealed an enrichment of genes involved in the 16p11.2 proximal deletion syndrome, driven by a large recurrent deletion (chr16:29,595,483-30,159,693) identified in 0.15% of endometrial cancer cases and 0.02% of control participants. Together, these data provide evidence that rare copy number variants have a role in endometrial cancer susceptibility and that the proximal 16p11.2 BP4-BP5 region contains 25 candidate risk gene(s) that warrant further analysis to better understand their role in human disease.

Artificial Light Increases Nighttime Prevalence of Predatory Fishes, Altering Community Composition on Coral Reefs - Emma Weschke; Jules Schligler; Isla Hely; Thibaut Roost; Jo‐Ann Schies; Ben Williams; Bartosz Dworzanski; Suzanne C. Mills; Ricardo Beldade; Stephen D. Simpson; Andrew N. Radford (Global Change Biology, 2024)
Artificial light at night (ALAN) is an anthropogenic pollutant that is intensifying and expanding in marine environments, but experimental studies of community‐level effects are generally lacking. The inshore, shallow, and clear‐water locations of coral reefs and their diverse photosensitive inhabitants make these ecosystems highly susceptible to biological disturbances; at the same time, their biodiversity and accessibility make them model systems for wider insight. Here, we experimentally manipulated ALAN using underwater LED lights on a Polynesian reef system to investigate the influence on localised nighttime fish communities compared to control sites without ALAN. We collected infrared video censuses of baseline communities prior to manipulation, which we repeated following short‐term (mean of three nights) and prolonged (mean of 25 nights) exposures to ALAN. Short‐term ALAN exposure did not induce any significant alterations to the nighttime fish community, but prolonged ALAN exposure increased nighttime species richness. Species compositions exposed to prolonged ALAN were more dissimilar from their baseline compared to control sites. The difference between community compositions at prolonged ALAN exposure and control sites was not apparent at the family level; instead, it was observed from the composition of trait guilds. Following prolonged ALAN exposure, more diurnal and nocturnal predatory species (piscivores, invertivores, and planktivores)—particularly those that are site‐attached or mobile within reefs—were present in nighttime assemblages. Our experimental findings show that coastal ALAN could cause trophic imbalances and circadian disturbances in localised nighttime reef fish communities. Given that community‐wide consequences were only apparent after prolonged ALAN exposure suggests that management of the duration of artificial lighting could potentially be used to reduce impacts on marine ecosystems.

Reporting population size in wastewater-based epidemiology: A scoping review - Mackay Price; Bradley S. Simpson; Benjamin J. Tscharke; Fahad Ahmed; Emma L. Keller; Hannah Sussex; Melanie Kah; Katarzyna Sila-Nowicka; Andrew Chappell; Cobus Gerber; Sam Trowsdale (Science of The Total Environment, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Monitoring the use of novel psychoactive substances in Australia by wastewater-based epidemiology - Emma L. Jaunay; Richard Bade; Kara R. Paxton; Dhayaalini Nadarajan; Daniel C. Barry; Yuze Zhai; Benjamin J. Tscharke; Jake W. O'Brien; Jochen Mueller; Jason M. White; Bradley S. Simpson; Cobus Gerber (Science of The Total Environment, 2024)

Corrigendum to “Using wastewater-based epidemiology to evaluate the scale of use of opioids” [Sci. Total Environ. 897 (2023), 165148] - Emma L. Jaunay; Bradley S. Simpson; Jason M. White; Cobus Gerber (Science of The Total Environment, 2024)

Using wastewater-based epidemiology to evaluate the relative scale of use of opioids - Emma L. Jaunay; Bradley S. Simpson; Jason M. White; Cobus Gerber (Science of The Total Environment, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

SCUBA noise alters community structure and cooperation at Pederson’s cleaner shrimp cleaning stations - Kieran P. McCloskey; Andrew N. Radford; Amelia Rose; Giorgio Casiraghi; Natalie Lubbock; Emma Weschke; Benjamin M. Titus; Dan A. Exton; Stephen D. Simpson (Frontiers in Marine Science, 2023)
Recreational SCUBA diving is widespread and increasing on coral reefs worldwide. Standard open-circuit SCUBA equipment is inherently noisy and, by seeking out areas of high biodiversity, divers inadvertently expose reef communities to an intrusive source of anthropogenic noise. Currently, little is known about SCUBA noise as an acoustic stressor, and there is a general lack of empirical evidence on community-level impacts of anthropogenic noise on coral reefs. Here, we conducted a playback experiment on Caribbean reefs to investigate impacts of SCUBA noise on fish communities and interspecific cooperation at ecologically important cleaning stations of the Pederson’s cleaner shrimp Ancylomenes pedersoni . When exposed to SCUBA-noise playback, the total occurrence of fishes at the cleaning stations decreased by 7%, and the community and cleaning clientele compositions were significantly altered, with 27% and 25% of monitored species being affected, respectively. Compared with ambient-sound playback, SCUBA-noise playback resulted in clients having to wait 29% longer for cleaning initiation and receiving 43% less cleaning; however, cheating, signalling, posing and time spent cleaning were not affected by SCUBA-noise playback. Our study is the first to demonstrate experimentally that SCUBA noise can have at least some negative impacts on reef organisms, confirming it as an ecologically relevant pollutant. Moreover, by establishing acoustic disturbance as a likely mechanism for known impacts of diver presence on reef animals, we also identify a potential avenue for mitigation in these valuable ecosystems.

Profile likelihood-based parameter and predictive interval analysis guides model choice for ecological population dynamics - Matthew J. Simpson; Shannon A. Walker; Emma N. Studerus; Scott W. McCue; Ryan J. Murphy; Oliver J. Maclaren (Mathematical Biosciences, 2023)

Contaminant pulse following wildfire is associated with shifts in estuarine benthic communities - Sally A. Bracewell; Thayanne L. Barros; Mariana Mayer-Pinto; Katherine A. Dafforn; Stuart L. Simpson; Emma L. Johnston (Environmental Pollution, 2023)

Drugs and Bugs: The Gut-Brain Axis and Substance Use Disorders - Sierra Simpson; Rio Mclellan; Emma Wellmeyer; Frederic Matalon; Olivier George (Journal of Neuroimmune Pharmacology, 2022)
Substance use disorders (SUDs) represent a significant public health crisis. Worldwide, 5.4% of the global disease burden is attributed to SUDs and alcohol use, and many more use psychoactive substances recreationally. Often associated with comorbidities, SUDs result in changes to both brain function and physiological responses. Mounting evidence calls for a precision approach for the treatment and diagnosis of SUDs, and the gut microbiome is emerging as a contributor to such disorders. Over the last few centuries, modern lifestyles, diets, and medical care have altered the health of the microbes that live in and on our bodies; as we develop, our diets and lifestyle dictate which microbes flourish and which microbes vanish. An increase in antibiotic treatments, with many antibiotic interventions occurring early in life during the microbiome's normal development, transforms developing microbial communities. Links have been made between the microbiome and SUDs, and the microbiome and conditions that are often comorbid with SUDs such as anxiety, depression, pain, and stress. A better understanding of the mechanisms influencing behavioral changes and drug use is critical in developing novel treatments for SUDSs. Targeting the microbiome as a therapeutic and diagnostic tool is a promising avenue of exploration. This review will provide an overview of the role of the gut-brain axis in a wide range of SUDs, discuss host and microbe pathways that mediate changes in the brain’s response to drugs, and the microbes and related metabolites that impact behavior and health within the gut-brain axis. Graphic Abstract

Evolving and Sustaining Ocean Best Practices to Enable Interoperability in the UN Decade of Ocean Science for Sustainable Development - Jay Pearlman; Pier Luigi Buttigieg; Mark Bushnell; Claudia Delgado; Juliet Hermes; Emma Heslop; Cora Hörstmann; Kirsten Isensee; Johannes Karstensen; Arno Lambert; Ana Lara-Lopez; Frank Muller-Karger; et al. (Frontiers in Marine Science, 2021)
The UN Decade of Ocean Science for Sustainable Development (Ocean Decade) challenges marine science to better inform and stimulate social and economic development while conserving marine ecosystems. To achieve these objectives, we must make our diverse methodologies more comparable and interoperable, expanding global participation and foster capacity development in ocean science through a new and coherent approach to best practice development. We present perspectives on this issue gleaned from the ongoing development of the UNESCO Intergovernmental Oceanographic Commission (IOC) Ocean Best Practices System (OBPS). The OBPS is collaborating with individuals and programs around the world to transform the way ocean methodologies are managed, in strong alignment with the outcomes envisioned for the Ocean Decade. However, significant challenges remain, including: (1) the haphazard management of methodologies across their lifecycle, (2) the ambiguous endorsement of what is “best” and when and where one method may be applicable vs. another, and (3) the inconsistent access to methodological knowledge across disciplines and cultures. To help address these challenges, we recommend that sponsors and leaders in ocean science and education promote consistent documentation and convergence of methodologies to: create and improve context-dependent best practices; incorporate contextualized best practices into Ocean Decade Actions; clarify who endorses which method and why; create a global network of complementary ocean practices systems; and ensure broader consistency and flexibility in international capacity development.

Evolving and Sustaining Ocean Best Practices and Standards for the Next Decade - Jay Pearlman; Mark Bushnell; Laurent Coppola; Johannes Karstensen; Pier Luigi Buttigieg; Francoise Pearlman; Pauline Simpson; Michele Barbier; Frank E. Muller-Karger; Cristian Munoz-Mas; Peter Pissierssens; Cyndy Chandler; et al. (Frontiers in Marine Science, 2019)

Using meta‐omics of contaminated sediments to monitor changes in pathways relevant to climate regulation - Simone C. Birrer; Katherine A. Dafforn; Melanie Y. Sun; Rohan B. H. Williams; Jaimie Potts; Peter Scanes; Brendan P. Kelaher; Stuart L. Simpson; Staffan Kjelleberg; Sanjay Swarup; Peter Steinberg; Emma L. Johnston (Environmental Microbiology, 2019)
Summary Microbially mediated biogeochemical processes are crucial for climate regulation and may be disrupted by anthropogenic contaminants. To better manage contaminants, we need tools that make real‐time causal links between stressors and altered microbial functions, and the potential consequences for ecosystem services such as climate regulation. In a manipulative field experiment, we used metatranscriptomics to investigate the impact of excess organic enrichment and metal contamination on the gene expression of nitrogen and sulfur metabolisms in coastal sediments. Our gene expression data suggest that excess organic enrichment results in (i) higher transcript levels of genes involved in the production of toxic ammonia and hydrogen sulfide and (ii) lower transcript levels associated with the degradation of a greenhouse gas (nitrous oxide). However, metal contamination did not have any significant impact on gene expression. We reveal the genetic mechanisms that may lead to altered productivity and greenhouse gas production in coastal sediments due to anthropogenic contaminants. Our data highlight the applicability of metatranscriptomics as a management tool that provides an immense breadth of information and can identify potentially impacted process measurements that need further investigation.

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

Characteristics of rural dust events shown to impact on asthma severity in Brisbane, Australia - S. Rutherford; Emma Clark; Grant McTainsh; R. Simpson; Charles Mitchell (International Journal of Biometeorology, 1999)